A baker's dozen real analog solutions for digital designers - Baker, Bonnie (Bonnie C.)
This book has been written to help digital engineers who need a few basic analog tools in their toolbox. For practicing digital engineers, students, educators and hands-on managers who are looking for the analog foundation they need to handle their daily engineering problems, this will serve as a valuable reference to the nuts-and-bolts of system analog design in a digital world. This book is a hands-on designer's guide to the most important topics in analog electronics, such as Analog-to-Digital and Digital-to-Analog conversion, operational amplifiers, filters, and integrating analog and digital systems. The presentation is tailored for engineers who are primarily experienced and/or educated in digital circuit design. This book will teach such readers how to "think analog" when it is the best solution to their problem. Special attention is also given to fundamental topics, such as noise and how to use analog test and measurement equipment, that are often ignored in other analog titles aimed at professional engineers.